Prevalence of Alzheimer’s disease pathology in the community - Dag Aarsland; Anita Lenora Sunde; Diego A. Tovar-Rios; Antoine Leuzy; Tormod Fladby; Henrik Zetterberg; Kaj Blennow; Kübra Tan; Giovanni De Santis; Yara Yakoub; Burak Arslan; Hanna Huber; et al. (Nature, 2026)
Abstract The prevalence of Alzheimer’s disease neuropathological changes (ADNCs), the leading cause of cognitive impairment, remains uncertain. Recent blood-based biomarkers enable scalable assessment of ADNCs 1 . Here we measured phosphorylated tau at threonine 217 in 11,486 plasma samples from a Norwegian population-based cohort of individuals over 57 years of age as a surrogate marker for ADNCs. The estimated prevalence of ADNCs increased with age, from less than 8% in people 58–69.9 years of age to 65.2% in those over 90 years of age. Among participants aged 70 years or older, 10% had preclinical Alzheimer’s disease, 10.4% had prodromal Alzheimer’s disease and 9.8% had Alzheimer’s disease dementia. Furthermore, among those 70 years of age or older, ADNCs were present in 60% of people with dementia, in 32.6% of those with mild cognitive impairment and in 23.5% of the cognitively unimpaired group. Our findings suggest a higher prevalence of Alzheimer’s disease dementia in older individuals and a lower prevalence of preclinical Alzheimer’s disease in younger groups than previously estimated 2 .